Reading skills for the first-year students at Vietnam Maritime University by implementing task-based language teaching - Nguyễn, Phương Hạnh (University of Languages and International Studies, 2017)
Reading is one of the most important skills in learning English. However, the teaching and learning reading skills in Vietnam in general and in Vietnam Maritime University in particular is still limited for some reasons. The purpose of this study was to examine the teaching and learning reading skills in Vietnam in general and in Vietnam Maritime University in particular.